2017
DOI: 10.1002/chem.201701402
|View full text |Cite
|
Sign up to set email alerts
|

A Bioinspired Organocatalytic Cascade for the Selective Oxidation of Amines under Air

Abstract: A bioinspired organocatalytic cascade reaction for the selective aerobic oxidative cross-coupling of primary amines to imines is described. This approach takes advantages of commercially available pyrogallol monomeric precursor to deliver low loadings of natural purpurogallin in situ, under air. This is further engaged in a catalytic process with the amine substrate affording, under single turnover, the active biomimetic quinonoid organocatalyst and the homocoupled imine intermediate, which is then converted i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 54 publications
0
19
0
Order By: Relevance
“…45 Based on this insight, we have developed a double biomimetic reaction pathway resulting in the formation of 1,2-disubstituted benzimidazoles. 46 The reaction sequence starts from inexpensive commercially available pyrogallol and allows, under ambient air, the in situ generation of not easily accessible natural purpurogallin, which is further engaged in the transamination process analogous to that reported in Scheme 16, for producing, under single turnover, the active biomimetic organocatalyst IMQ′ (Scheme 17). Dynamic transimination followed by intramolecular cyclization and subsequent oxidation reactions produced the 1,2-disubstituted benzimidazole derivatives.…”
Section: Short Review Syn Thesismentioning
confidence: 99%
“…45 Based on this insight, we have developed a double biomimetic reaction pathway resulting in the formation of 1,2-disubstituted benzimidazoles. 46 The reaction sequence starts from inexpensive commercially available pyrogallol and allows, under ambient air, the in situ generation of not easily accessible natural purpurogallin, which is further engaged in the transamination process analogous to that reported in Scheme 16, for producing, under single turnover, the active biomimetic organocatalyst IMQ′ (Scheme 17). Dynamic transimination followed by intramolecular cyclization and subsequent oxidation reactions produced the 1,2-disubstituted benzimidazole derivatives.…”
Section: Short Review Syn Thesismentioning
confidence: 99%
“…Imines are an important class of compounds with ample use in pharmaceutical and chemical industry, as they are key precursors for many biologically active heterocycles . Many of the reported procedures for oxidative cross‐coupling and homocoupling of amines use noble‐metal catalysts such as Co, Au, Pd, Ru, and V . Recently, many research groups focused on less expensive non‐noble catalysts, including Cu, Fe, Al,[21d], and others .…”
Section: Introductionmentioning
confidence: 99%
“…However, traces of heavy metals in the final product still represent a major issue. [21d], [21e], Due to this fact, metal‐free catalytic procedures gained much attention in the last years. It has been shown that graphite oxide and doped porous carbon[8b], are also suitable catalysts for amine oxidation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[15][16][17] Moreover,l ow-potential o-quinone-type catalysts were recently shownt oe nablem anifold (bioinspired) aerobic oxidations. [18][19][20][21][22][23][24][25][26] Despite of the outstandings uccesss tory of quinones, some drawbacks oppose their large-scale applications.H ence cyanoor halo-substituted benzoquinones like CA are highly toxic, as they induce reactiveo xygen speciesa nd oxidative stress, showinga ni nflammatory response both in vivo and in vitro. [27] Moreover,the recycling of the quinones is sometimesproblematic due to side reactions.…”
mentioning
confidence: 99%